Answer:
-1/6
Step-by-step explanation:
1/6-1/3
1/6-1×2/3×2
1/6-2/6
1-2/6
-1/6
3∅ can be rewritten as (2∅+∅)
sin(3∅) = sin(2∅ + ∅<span>)
Opening brackets on the right hand side;
= sin2</span>∅ cos ∅ + cos2∅sin<span>∅
</span><span>This simplifies to;
= 2sin</span>∅cos^2∅ + sin∅ (1- 2sin^2∅<span>)
= sin</span>∅ (2cos^2∅ + 1 - 2sin^2∅<span>)
= sin</span>∅ (2(1 - sin^2∅) +1-2sin^2∅<span>)
= 3sin</span>∅ - 4sin^3<span>∅</span>
Answer:
x = 6
Step-by-step explanation:
Assuming the equation is
-
= - 4
Multiply through by 6 ( the LCM of 3 and 2 ) to clear the fractions
2(2x + 3) - 9x = - 24
4x + 6 - 9x = - 24
- 5x + 6 = - 24 ( subtract 6 from both sides )
- 5x = - 30 ( divide both sides by - 5 )
x = 6
Answer:
6/7
Step-by-step explanation:
Answer:
C
Step-by-step explanation:
Note that (f + g)(x) = f(x) + g(x)
f(x) + g(x)
= 4x + 1 + x² - 5 ← collect like terms
= x² + 4x - 4 → C